A comparative analysis of different types of flood shelters in Bangladesh - Mallick, Professor Fuad Hassan; Rahman, M Aminur; Rahman, Tahmina; Rahman, Professor Mohammad Rezaur; Mondal, M Shahjahan (Department of Architecture, BRAC University, 2012)
Technical Analysis Team: Institute of Water and Flood Management (IWFM) and Bangladesh University of Engineering and Technology (BUET). Socio-economic and Cultural Analysis Team: Postgraduate Programs in Disaster Management (PPDM). BRAC University.